Hypercrosslinked microporous polymer sorbents for the efficient recycling of a soluble acid catalyst in cellulose hydrolysis. Issue 10 (2nd May 2018) - Woodward, Robert T.; Kessler, Martin; Lima, Sérgio; Rinaldi, Roberto
Abstract : The use of hypercrosslinked microporous polymers overcomes the difficulties in the recycling of soluble acid catalysts within the lignocellulosic biorefinery improving the sustainability of cellulose hydrolysis and several other transformations. Abstract : Difficulties in the recycling of soluble acid catalysts within the lignocellulosic biorefinery constitute a serious issue to the sustainability of cellulose hydrolysis and several other transformations. Herein, we demonstrate a simple and effective method for the removal and recovery of p -toluenesulfonic acid (p-TSA) employed as a replacement of H2 SO4 in the saccharification of cellulose by a mechanocatalytic route. p-TSA is recovered from its diluted aqueous solutions using a non-expensive hypercrosslinked polymer adsorbent. In a batch process, around 97% p-TSA acid was removed from a 5 mM solution after exposure to the hypercrosslinked polymer. Notably, a flow-through process was able to selectively remove the catalyst completely from even lower initial concentrations. Importantly, the efficient recovery of the p-TSA is achieved by washing the spent polymer with methanol. In the purification of a stream derived from the saccharification of cellulose, the extraction of p-TSA catalyst in addition to 5-hydroxymethylfurfural (HMF) and furfural was also achieved. With the rational choice of solvents, p-TSA and furfurals were separately recovered. In the broader context, the current findings represent a step forward towards the acid management from the acid-catalyzed saccharification of cellulose. Moreover, this approach is conducive for the purification of sugars for bioconversion in which even low levels of furfurals may exert a strong inhibitory effect upon yeast cultures.